From policy to practice : sustainable innovations in school leadership preparation and development - Sanzo, Karen (UCEA leadership series., 2014)
The School Leadership Program (SLP) is a federal grant sponsored by the United States Department of Education. A hallmark of the grant is the connectivity between various agencies to provide quality leadership preparation and development programs for aspiring and current school leaders. These collaborative efforts involve community and educational stakeholders including districts, universities, city agencies, not-for-profit entities, foundations, private academic organizations, and others involved in the development of school leaders. Since its inception in 2002, over one hundred grants have been funded. This edited book's purpose is to share innovative, research-based practices from the federally funded grants that are sustainable after the life of the grant and are able to be used throughout the field for preparing and developing aspiring and current school leaders. This book features the work of current and past grantees around their innovative practices and lessons learned about school leadership preparation and development, especially around the issue of sustainability of these practices upon completion of the grant. SLP Grantees share practical, usable lessons learned from their experiences with the grants, based on their research, project data, and practical experience.